Pengembangan Aplikasi Pelatihan dan Sertifikasi Pegawai pada Pusdiklat PT. Bank X berbasis Web - Robit Hussalam; Yulia Ery Kurniawati (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2023)
This study aims to develop a web-based employee training and certification application at the Education and Training Center of Bank X. Currently, the Education and Training Center of Bank X are having problems managing data and information for employee training and certification. The application is expected to help collect data, training, and certification and convey accurate information. The software development life cycle used is Rational Unified Process (RUP). It has several processes during the development, namely Business Modelling, Requirements, Analysis and Design, Implementation, Testing, and Development. The application uses PHP programming language with CodeIgniter and MySQL database. All software functionality can run well based on the Black Box Testing results. The User Acceptance Test (UAT) results on users, both admin and participants, show that the application is easy to understand and can help provide information related to employee training at the Education and Training Center of Bank X.